Pengaruh Komunikasi Internal Terhadap Kinerja Karyawan - Rizkyana, Neng Putri Febbyalika; Oktaria, Rina; Putra, Toby Farda; Muntaz, Rizal; Baso, Andi Muhammad Fauzan; Ilham, Muhamad; Laksana, April (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Internal communication plays a role in supporting employee performance within an organization. This study aims to analyze the effect of internal communication on employee performance with a focus on how effective information delivery can improve productivity and collaboration. This study uses a qualitative literature study method, by reviewing various secondary sources such as scientific journals, academic articles, and relevant books. The data collected shows that open, clear, and transparent internal communication can strengthen employee understanding of their roles and responsibilities, while building harmonious working relationships. The results of this literature review confirm that good internal communication management is a strategic element in improving operational efficiency and overall organizational success.